Accounting for institutional quality in global forest modeling. (April 2018) - Wehkamp, Johanna; Pietsch, Stephan Alexander; Fuss, Sabine; Gusti, Mykola; Reuter, Wolf Heinrich; Koch, Nicolas; Kindermann, Georg; Kraxner, Florian
Abstract: The current state of the art in modeling forest cover change is to combine a detailed representation of biophysical processes with economic decision-making principles. Yet, there is an increasing consensus that the quality of political institutions is another relevant component in determining forest cover change patterns. In this paper, the Global Forest Model is used to analyze whether including an index, measuring the capacity of political institutions to guarantee sustainable natural resource management, allows to improve the precision of the modeled forest cover trend. The analysis shows that incorporating the index indeed allows reducing the gap between the estimated and observed forest cover trends for the 2000 to 2010 calibration period. Highlights: Index measuring the capacity of political institutions to guarantee sustainable natural resource management. Application of index to the Global Forest Model and reduction of the models unexplained factors. Discussion of the role of institutional quality in forest cover change modelling.